Method for measuring compaction density of battery pole piece

By conducting rolling pressure tests on the battery pole plate with different test pressures, the compaction density is measured and the trend line is constructed, and the trend inflection point is screened to determine the critical compaction density of the broken belt, the problem of difficulty in obtaining the critical compaction density of the polar segment belt in the prior art is solved, and fast and accurate density acquisition is achieved, reducing rework and waste.

CN119880694APending Publication Date: 2025-04-25ENVISION RUITAI DYNAMICS TECH (SHANGHAI) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311384683.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively obtain the critical compaction density of the battery pole sheet under the roller pressing process, resulting in a long period of time and huge resource consumption during the process of increasing the compaction density.

Method used

By performing rolling tests on multiple pole pieces with different test pressures, the compaction density is measured, and a test pressure-compact density trend line is constructed, and the trend inflection point is screened to determine the critical compaction density of the pole piece with broken belt.

Benefits of technology

This method can quickly and accurately obtain the maximum bearing compression level during the polar sheet rolling process, reduce rework and waste, and guide the subsequent production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119880694A_ABST
    Figure CN119880694A_ABST
Patent Text Reader

Abstract

The invention provides a method for measuring the compaction density of battery pole pieces, and belongs to the technical field of batteries, the method for measuring the compaction density comprises the following steps: taking a plurality of pole pieces as test samples; rolling the test sample at different test pressures, and measuring the compaction density of the rolled test sample; constructing a test pressure intensity-compaction density trend line according to the test pressure intensity when the test sample is subjected to rolling and the compaction density after the test sample is subjected to rolling; and screening a trend inflection point from the test pressure intensity-compaction density trend line, and taking the compaction density corresponding to the trend inflection point as the broken zone critical compaction density of the pole piece. According to the method, the maximum bearable compaction level in the pole piece rolling process can be obtained through a small number of rolling tests, the pole piece broken belt critical compaction density can be accurately obtained to guide the subsequent production process of the pole piece, and the reworking and waste conditions caused by the fact that the compaction design is higher than the manufacturing process level are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for measuring the compaction density of a battery pole piece. Background Art

[0002] Rolling is an important part of the lithium battery preparation process. Its function is to increase the compaction density of the active material layer coated on the surface of the electrode and make the thickness of the active material layer consistent. This process can effectively improve the energy density of the prepared battery and make the battery have better long-term performance.

[0003] Since the increase in the compaction density of the pole piece is beneficial to improving the dynamic performance of the battery, the current battery has continuously increased the requirements for the compaction density of the pole piece in order to obtain higher energy density and long-term performance. In the existing process, the compaction density of the pole piece cannot be increased indefinitely due to the limitations of the rolling process and the pole piece material. When continuously pursuing higher compaction density, the pole piece will often break at a certain critical compaction density. In order to obtain the maximum critical compaction density that the pole piece can withstand, a large number of experiments are often required. The entire adjustment process has a long cycle and consumes huge resources. If the critical value of the compaction that can be achieved by the pole piece can be determined in the early stage, the maximum tolerable compaction level in the subsequent production process can be guided, thereby reducing the rework and waste caused by the compaction being too high and the process level not being achieved.

[0004] Therefore, it is necessary to design a method for measuring the compaction density of battery electrodes to solve the above problems. Summary of the invention

[0005] In view of the above shortcomings of the prior art, the present invention provides a method for measuring the compaction density of a battery pole piece to solve the technical problem that it is difficult to obtain the critical compaction density of a battery pole piece during a rolling process in the prior art.

[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides a method for measuring the compaction density of battery pole pieces, and the test method comprises: using multiple pole pieces as test samples; rolling the test samples at different test pressures, and measuring the compaction density of the test samples after rolling; constructing a test pressure-compaction density trend line according to the test pressure when the test samples are subjected to rolling and the compaction density after rolling; selecting a trend inflection point from the test pressure-compaction density trend line, and using the compaction density corresponding to the trend inflection point as the critical compaction density of the pole piece for breaking.

[0007] In an example of the present invention, the trend inflection point is a slope inflection point on the test pressure-compaction density trend line.

[0008] In an example of the present invention, the plurality of pole pieces have the same current collector and an active material layer coated on the current collector.

[0009] In one example of the present invention, the measured compaction density is ρ=(M-M0) / (S×(H-H0)), wherein M is the mass of the pole piece, H is the thickness of the pole piece after rolling, M0 is the mass of the current collector, S is the surface area of ​​the current collector, and H0 is the thickness of the current collector.

[0010] In one example of the present invention, when the pole piece is a positive pole piece, the thickness of the current collector of the positive pole piece is 11 μm to 16 μm, and the thickness of the active material layer coated on the current collector is 30 μm to 90 μm; when the pole piece is a negative pole piece, the thickness of the current collector of the negative pole piece is 4 μm to 7 μm, and the thickness of the active material layer coated on the current collector is 40 μm to 100 μm.

[0011] In one example of the present invention, the test pressure is P n =P1+(N-1)×ΔP, N≥3; the interval pressure ΔP is 0.01 to 0.5Mpa.

[0012] In an example of the present invention, the P1 is an initial test pressure, and the P1 is 5 to 10 MPa.

[0013] In an example of the present invention, the plurality of test pressures have the same interval pressure ΔP.

[0014] In an example of the present invention, during the rolling process, the test pressure is adjusted by controlling the gap width of the rollers that roll the pole piece in the rolling equipment.

[0015] In an example of the present invention, the measuring method further includes: folding the test sample after rolling until light is transparent, and recording the number of times the test sample is folded; comparing the relationship between the number of times the test sample is folded and the change in the compaction density, and evaluating the accuracy of the obtained critical compaction density of the broken belt.

[0016] The measuring method of the present invention uses different rolling test pressures to roll multiple groups of pole pieces, records the compaction density of multiple groups of pole pieces after rolling, obtains the numerical relationship between the test pressure and the compaction density, and constructs a test pressure-compaction density trend line based on the numerical relationship. Based on the obvious change in the compaction density change rate before and after the hardening of the active material layer during the rolling process of the pole piece, the compaction density corresponding to the rolling hardening of the pole piece is obtained by screening the trend inflection point on the test pressure-compaction density trend line, that is, the critical compaction density of the pole piece breaking during the rolling process. This measuring method can obtain the maximum tolerable compaction level during the rolling process of the pole piece with a small amount of rolling tests, and accurately obtain the critical compaction density of the pole piece breaking, so as to guide the subsequent production process of the pole piece and reduce the rework and waste caused by the compaction design being higher than the process level. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 It is a schematic flow chart of a method for measuring the compaction density of a battery electrode in one embodiment of the present invention;

[0019] Figure 2 A test pressure-compaction density trend line diagram in one embodiment of the present invention;

[0020] Figure 3 A roller gap parameter-compacted density trend line diagram in one embodiment of the present invention;

[0021] Figure 4 It is a schematic diagram of the operation of a method for folding a pole piece in one embodiment of the present invention;

[0022] Figure 5 It is a flow chart of a method for verifying the critical compaction density of a broken belt in one embodiment of the present invention. DETAILED DESCRIPTION

[0023] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0024] It should be noted that, in the absence of conflict, the features in the following examples and embodiments can be combined with each other. It should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments rather than to limit the scope of the present invention. The test methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0025] For simplicity, only some numerical ranges are explicitly disclosed herein, and each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unspecified range.

[0026] Through the invention and research, it is found that in the rolling process of the pole piece, the active material layer coated on the pole piece will rapidly increase the compaction density of the pole piece at the beginning of rolling because the material particles in the layer fill the vacancies with each other. However, after the compaction density of the pole piece is increased to a certain extent, the compression deformation resistance is generated in the active material layer. At this time, when the pole piece is subjected to the same level of rolling, the degree of change in the compaction density of the pole piece will become much smaller, until the active material layer of the pole piece hardens, and the change in the compaction density of the pole piece is close to stopping. In addition, since there is still a certain traction force on the pole piece during the rolling process, the strip will break before hardening occurs. Therefore, the present invention provides a method for measuring the compaction density of a battery pole piece, which can obtain the compaction density of the pole piece when it hardens based on the change law of the compaction density of the pole piece during the rolling process by screening the inflection point of the change trend of the compaction density of the pole piece, that is, obtain the critical compaction density of the pole piece breaking during the rolling process.

[0027] like Figure 1 As shown, the present invention provides a method for measuring the compaction density of a battery pole piece, and the measuring method comprises the following steps:

[0028] S101, using multiple pole pieces as test samples;

[0029] S102, rolling the test sample at different test pressures, and measuring the compaction density of the test sample after rolling;

[0030] S103, constructing a test pressure-compacted density trend line according to the test pressure when the test sample is subjected to roller pressing and the compacted density after roller pressing;

[0031] S104, selecting a trend inflection point from the test pressure-compaction density trend line, and taking the compaction density corresponding to the trend inflection point as the critical compaction density of the pole piece for breaking the band.

[0032] The method for measuring the compaction density of battery pole pieces is to obtain the data relationship between the compaction density of the pole pieces after rolling and the test pressure by performing a rolling test on multiple groups of pole pieces at different test pressures; a test pressure-compaction density trend line is obtained based on the data relationship, a trend inflection point is screened out in the test pressure-compaction density trend line, and based on the compaction density change law during the rolling of the pole pieces, the compaction density corresponding to the trend inflection point is used as the compaction density when the pole pieces are hardened by rolling, that is, the compaction density corresponding to the trend inflection point is used as the critical compaction density of the breaking band corresponding to the pole piece.

[0033] In step S101, a plurality of identical pole pieces are selected as test samples. The pole pieces in the test samples should have the same current collector and the same active material layer coated on the current collector, wherein the same current collector refers to a current collector with the same material and thickness, and the same active material layer refers to an active material layer with the same material and thickness.

[0034] It should be noted that there is no specific limitation on the type of pole piece used in the present invention, and the pole piece corresponding to the field can be selected as the test sample for testing according to the actual test needs.

[0035] For example, in some embodiments, when the test sample is a positive electrode plate, the positive electrode plate can use an aluminum foil with a thickness of 11 μm to 16 μm as a current collector, the thickness of the active material layer coated on the current collector is 30 μm to 90 μm, the active material layer is formed by coating the positive electrode slurry on the current collector, and the positive electrode slurry is formed by mixing the positive electrode material, the positive electrode binder and the positive electrode conductor. As an example, the positive electrode material is selected from any one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, or a combination of at least two of them. The positive electrode binder is selected from polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE), etc., and the positive electrode conductor is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more of them mixed in any proportion.

[0036] When the test sample is a negative electrode sheet, the negative electrode sheet can use a copper foil with a thickness of 4 μm to 7 μm as a current collector, the thickness of the active material layer coated on the current collector is 30 μm to 90 μm, and the active material layer is formed by coating the negative electrode slurry on the current collector. The negative electrode slurry is formed by mixing the negative electrode material, the electrode conductive agent, the negative electrode binder and the negative electrode thickener. As an example, the negative electrode material is selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, pure silicon, silicon oxide compound, silicon carbon compound, and carbon silicon composite material, preferably a carbon silicon composite material, such as a combination of silicon oxide and artificial graphite. The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more of them mixed in any proportion. The negative electrode binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR) or a combination thereof mixed in any proportion; the negative electrode thickener is selected from carboxymethyl cellulose, which may be sodium carboxymethyl cellulose (CMC-Na) or lithium carboxymethyl cellulose (CMC-Li).

[0037] In step S102, after the test sample is rolled at different test pressures, the rolled test sample is sampled, and after the relevant parameters of the pole piece sample are weighed, the compaction density ρ of the pole piece after rolling is calculated according to the following formula, ρ = (M-M0) / (S×(H-H0)); wherein M is the mass of the pole piece sample, H is the thickness of the pole piece sample after rolling, M0 is the mass of the current collector in the pole piece sample, S is the surface area of ​​the current collector in the pole piece sample, and H0 is the thickness of the current collector in the pole piece sample.

[0038] Step S103 includes constructing a test pressure-compaction density coordinate system with the test pressure of the test sample being rolled as the ordinate and the compaction density of the test sample after rolling as the abscissa; filling the corresponding data of the test pressure and compaction density obtained from multiple groups of pole piece tests into the test pressure-compaction density coordinate system in the form of data scatter points, and connecting the data scatter points in sequence to obtain a test pressure-compaction density trend line.

[0039] like Figure 2 As shown, in step S104, due to the obvious change in the rate of increase of the compaction density of the active material layer of the pole piece due to rolling before and after hardening, two fitting lines with obvious slope differences will appear on the test pressure-compaction density trend line based on scatter point fitting, and the intersection between the two fitting lines is the slope inflection point on the test pressure-compaction density trend line, which is also the trend inflection point on the test pressure-compaction density trend line. Then, the compaction density corresponding to the trend inflection point is taken as the critical compaction density of the band break, that is, the compaction density when the pole piece hardens, and the critical compaction density of the band break of this type of pole piece can be measured. The critical compaction density of the band break can be used as the upper limit of the compaction density of the pole piece rolling process to provide guidance for subsequent production. The critical compaction density of the band break is the maximum compaction density that the pole piece can withstand under the rolling process. If the compaction density of the pole piece after rolling is greater than the critical compaction density of the band break, the pole piece is very likely to break when rolling.

[0040] In step S102, the test pressure applied to the multiple sets of electrodes in the test sample is P n =P1+(N-1)×ΔP, N≥3; wherein the initial test pressure P1 is 5 to 10 MPa, for example, the initial test pressure P1 can be 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa or 10 MPa; each test pressure P n The interval pressure ΔP between them is 0.01 to 0.5 MPa, for example, the interval pressure ΔP can be 0.01 MPa, 0.02 MPa, 0.04 MPa, 0.05 MPa, 0.06 MPa, 0.08 MPa, 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa or 0.5 MPa.

[0041] In some embodiments, in step S102, the multiple test pressures applied to the multiple groups of pole pieces in the test sample have the same interval pressure ΔP. Among them, the pole pieces are subjected to roller pressure tests with multiple test pressures having the same interval pressure ΔP, which is more convenient for the test pressure-compacted density trend line constructed by the scatter plot to show the change trend of the compacted density with the increase of the test pressure, and is also more convenient for selecting the trend inflection point from the test pressure-compacted density trend line.

[0042] In some embodiments, in step S102, during the rolling test, the test pressure applied to the electrode sheet is adjusted by controlling the gap width of the rollers in the rolling device. The test pressure applied to the electrode sheet by the rollers can be finely adjusted by changing the gap width of the rollers.

[0043] In addition, the method for measuring the compaction density of the battery pole piece also includes a verification step, which uses the light transmittance of the pole piece after rolling and folding as a judgment standard. Specifically, multiple groups of test samples after rolling are symmetrically folded in half multiple times until light is transparent. Since the fewer times the pole piece is folded in half until light is transparent, the higher the degree of hardening of the pole piece, the greater the brittleness, and the less conducive to processing and production. Therefore, this verification determines the degree of hardening of each group of test samples after rolling by comparing the number of times the test sample is folded in half until light is transparent, and obtains the compaction density corresponding to the hardening of the pole piece, thereby verifying whether the critical compaction density of the broken belt obtained by the measurement method is accurate.

[0044] Specifically, Figure 5 As shown, the verification step includes the following steps:

[0045] S201, folding the rolled test sample in half until light is transparent, and recording the number of times the test sample is folded in half;

[0046] Specifically, firstly, samples are taken from the test samples after rolling, and the obtained electrode samples are cut into a symmetrical shape that is easy to fold in half, such as an isosceles triangle, rectangle or circle; then, Figure 4 The folding method shown is to first fold the pole piece sample 180° symmetrically along the center, and then unfold it to observe whether there is any light leakage. If not, continue to fold it in the opposite direction to 180°, and then unfold it to observe whether there is any light leakage. If not, fold it in the direction of the first fold to 180°, and then unfold it to observe it under the light. Repeat this process and record the number of folding times when light leakage occurs.

[0047] S202, comparing the relationship between the number of folding times of the test sample and the compaction density, and evaluating the accuracy of the obtained critical compaction density of the broken belt.

[0048] Specifically, after the pole piece is rolled and hardened, the number of times it is folded in half to become light transmittance is reduced compared to before hardening. Therefore, by comparing the relationship between the number of folding times and the compaction density of the test sample, the compaction density that increases to when the number of folding times of the test sample becomes less is screened out, and the compaction density is compared with the measured critical compaction density for band break. If the compaction density is closest to the critical compaction density for band break, it proves that the obtained critical compaction density for band break is accurate.

[0049] The technical scheme of the present invention is described in detail by the following examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0050] Example 1

[0051] S101. Select a plurality of identical positive electrode sheets that have not been rolled as test samples, and mark them as sample A, sample B, sample C, sample D, sample E and sample F respectively; wherein the positive electrode sheets used as the test samples all use aluminum foil with a thickness of 12 μm as the current collector, and an active material layer with a thickness of 50 μm is coated on the current collector, and the active material layer is formed by coating a slurry of lithium iron phosphate, carbon black (Super P), and polyvinylidene fluoride (PVDF) mixed in a weight ratio of 97:1.5:1.5 on the current collector;

[0052] S102. Use a rolling device to roll sample A, sample B, sample C, sample D, sample E and sample F at test pressures of 6.0Mpa, 6.4Mpa, 6.7Mpa, 7.0Mpa, 7.2Mpa and 7.3Mpa respectively, and measure the compaction density of sample A, sample B, sample C, sample D, sample E and sample F after rolling; wherein, the rolling device can use conventional rolling equipment in the field, such as roller presses of brands such as Pioneer and Liyuanheng. When using the upper rolling device for rolling, the roller gap width can be adjusted by changing the roller gap parameters on the operation panel of the rolling device, thereby adjusting the test pressure applied by the roller to the electrode.

[0053] S103, the vertical coordinate of the test pressure of the test sample during rolling, and the horizontal coordinate of the compaction density of the test sample after rolling, to construct a test pressure-compaction density coordinate system; according to the data relationship between the test pressure and the compaction density after rolling of sample A, sample B, sample C, sample D, sample E and sample F, the corresponding data of the test pressure and compaction density obtained by the test of sample A, sample B, sample C, sample D, sample E and sample F are filled into the test pressure-compaction density coordinate system in the form of data scatter points, and the data scatter points are connected in sequence, so as to obtain the test pressure-compaction density trend line of the pole piece;

[0054] S104, selecting a trend inflection point from the test pressure-compaction density trend line, and taking the compaction density corresponding to the trend inflection point as the critical compaction density of the pole piece.

[0055] The test data of the test pressure during rolling of the test sample and the compaction density after rolling in Example 1 are shown in Table 1.

[0056] Table 1: Test pressure during rolling and compaction density after rolling of sample A, sample B, sample C, sample D, sample E and sample F in Example 1

[0057]

[0058] Among them, the roll gap width operating parameters in Table 1 are virtual parameters on the rolling equipment, and do not represent the actual roll gap width of the rolling equipment, but can only represent the adjustment range of the roll gap width. The roll gap operating parameters can also be used to replace the test pressure to construct a roll gap parameter-compaction density trend line when the test pressure is not convenient to count. The roll gap parameter-compaction density trend line has the same trend change as the test pressure-compaction density trend line.

[0059] According to Table 1, the corresponding data of the test pressure and compaction density of sample A, sample B, sample C, sample D, sample E and sample F are filled into the test pressure-compaction density coordinate system in the form of scattered points, and the test pressure-compaction density trend line is formed based on the scattered point fitting. The constructed test pressure-compaction density trend line is as follows: Figure 2 As shown, it can be clearly seen that the slopes of the fitting line at point AD and the fitting line at point EF are significantly different, so it can be judged that work hardening occurs when the compaction density of the pole piece increases to near point D. Based on this classification, the AD point data and the EF point data are fitted to make trend lines. Since the AD point fitting line and the EF point fitting line can respectively represent the compaction density changes during the rolling process before and after the pole piece is hardened, the intersection of the AD point fitting line and the EF point fitting line is the trend inflection point of the trend line. Based on the data in Table 1, the formulas of the AD point fitting line and the EF point fitting line are fitted, and the intersection point is taken to obtain the critical compaction density of the broken band corresponding to the trend inflection point, which is 2.588g / cm 3 .

[0060] In addition, according to the data shown in Table 1, the corresponding data of the roll gap width operating parameters and compaction density of sample A, sample B, sample C, sample D, sample E and sample F can be filled into the roll gap parameter-compaction density coordinate system in the form of scattered points in the same way, and the roll gap parameter-compaction density trend line can be generated by fitting, such as Figure 2 and Figure 3 As shown in the figure, the constructed roller gap parameter-compaction density trend line and the test pressure-compaction density trend line have the same compaction density change trend, where the slopes of the AD point fitting line and the EF point fitting line are obviously different. By fitting the roller gap parameter-compaction density trend line to obtain the intersection of the AD point fitting line and the EF point fitting line, the same critical compaction density of the broken belt can be measured.

[0061] Example 2

[0062] Furthermore, the accuracy of the critical compaction density of the broken belt is evaluated through the verification step. The verification step includes:

[0063] S201, folding sample A, sample B, sample C, sample D, sample E and sample F in half for multiple times until light is transparent, and recording the number of times sample A, sample B, sample C, sample D, sample E and sample F are folded in half;

[0064] S202. Compare the changing trends of the number of times the light is folded and the compaction density in the test samples, screen out the compaction density when the number of folds begins to decrease in sample A, sample B, sample C, sample D, sample E and sample F, and compare the compaction density with the measured critical compaction density of the broken band. If the two values ​​are close, it proves that the obtained critical compaction density of the broken band is accurate.

[0065] The test results of the folded samples in Example 2 are shown in Table 2.

[0066] Table 2: Number of folds corresponding to light transmission of samples A, B, C, D, E and F in Example 2

[0067] Group Transparent fold times <![CDATA[Compaction density (g / cm 3 )]]> Sample A 50% off 2.451 Sample B 50% off 2.499 Sample C 50% off 2.528 Sample D 50% off 2.556 Sample E 60% off 2.572 Sample F 70% off 2.598

[0068] From the test results of the verification step shown in Table 2, it can be seen that when the compaction density of the electrode is increased from 2.45g / cm 3 Increase to the critical compaction density of 2.588g / cm 3 2.572g / cm 3 When the pole piece is folded twice to transmit light, the number of times it is folded begins to decrease by 1 fold. When the compaction density of the pole piece exceeds the critical compaction density of 2.588g / cm 3 2.598g / cm 3 When the pole piece is folded in half for light transmission, the number of times it is folded in half decreases by another 1 fold, which indicates that the value of the critical compaction density of the broken belt measured in Example 1 is accurate.

[0069] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for measuring the compaction density of a battery pole piece, characterized in that: include: Use multiple pole pieces as test samples; Rolling the test sample at different test pressures, and measuring the compaction density of the test sample after rolling; constructing a test pressure-compacted density trend line according to the test pressure when the test sample is subjected to roller pressing and the compacted density after roller pressing; A trend inflection point is selected from the test pressure-compaction density trend line, and the compaction density corresponding to the trend inflection point is used as the critical compaction density of the pole piece for breaking the band.

2. The method for measuring the compaction density of a battery pole piece according to claim 1, characterized in that: The trend inflection point is the slope inflection point on the test pressure-compaction density trend line.

3. The method for measuring the compaction density of a battery pole piece according to claim 1, characterized in that: The plurality of pole pieces have the same current collector and an active material layer coated on the current collector.

4. The method for measuring the compaction density of a battery pole piece according to claim 3, characterized in that: When the pole piece is a positive pole piece, the thickness of the current collector of the positive pole piece is 11μm to 16μm, and the thickness of the active material layer coated on the current collector is 30μm to 90μm; when the pole piece is a negative pole piece, the thickness of the current collector of the negative pole piece is 4μm to 7μm, and the thickness of the active material layer coated on the current collector is 40μm to 100μm.

5. The method for measuring the compaction density of a battery pole piece according to claim 3, characterized in that: The measured compaction density is ρ=(M-M0) / (S×(H-H0)), wherein M is the mass of the pole piece, H is the thickness of the pole piece after rolling, M0 is the mass of the current collector, S is the surface area of ​​the current collector, and H0 is the thickness of the current collector.

6. The method for measuring the compaction density of a battery pole piece according to claim 1, characterized in that: The test pressure is P n =P1+(N-1)×ΔP, N≥3; the interval pressure ΔP is 0.01 to 0.5Mpa.

7. The method for measuring the compaction density of a battery pole piece according to claim 6, characterized in that: The P1 is an initial test pressure, and the P1 is 5 to 10 MPa.

8. The method for measuring the compaction density of a battery pole piece according to claim 6, characterized in that: The plurality of test pressures have the same interval pressure ΔP.

9. The method for measuring the compaction density of a battery pole piece according to claim 1, characterized in that: During the rolling process, the test pressure is adjusted by controlling the gap width of the rollers used to roll the pole piece in the rolling equipment.

10. The method for measuring the compaction density of a battery pole piece according to claim 1, characterized in that: The detection method also includes: Folding the rolled test sample in half until light is transparent, and recording the number of times the test sample is folded in half; The relationship between the number of folding times of the test sample and the compaction density is compared to evaluate the accuracy of the obtained critical compaction density of the broken belt.